Syntenin regulates hepatitis C virus sensitivity to neutralizing antibody by promoting E2 secretion through exosomes - Deng, Libin; Jiang, Wang; Wang, Xiaoning; Merz, Andreas; Hiet, Marie-Sophie; Chen, Yujie; Pan, Xiaoyu; Jiu, Yaming; Yang, Yu; Yu, Bowen; He, Yongning; Tu, Zhengkun; et al. (Journal of hepatology, 2019)
Background & Aims - Assembly of infectious hepatitis C virus (HCV) particles is known to involve host lipoproteins, giving rise to unique lipo-viro-particles (LVPs), but proteome studies now suggest that additional cellular proteins are associated with HCV virions or other particles containing the viral envelope glycoprotein E2. Many of these host cell proteins are common markers of exosomes, most notably the intracellular adaptor protein syntenin, which is required for exosome biogenesis. We aimed to elucidate the role of syntenin/E2 in HCV infection. - Methods - Using cell culture-derived HCV, we studied the biogenesis and function of E2-coated exosomes in both hepatoma cells and primary human hepatocytes (PHHs). - Results - Knockout of syntenin had a negligible impact on HCV replication and virus production, whereas ectopic expression of syntenin at physiological levels reduced intracellular E2 abundance, while concomitantly increasing the secretion of E2-coated exosomes. Importantly, cells expressing syntenin and HCV structural proteins efficiently released exosomes containing E2 but lacking the core protein. Furthermore, infectivity of HCV released from syntenin-expressing hepatoma cells and PHHs was more resistant to neutralization by E2-specific antibodies and chronic-phase patient serum. We also found that high E2/syntenin levels in sera correlate with lower serum neutralization capability. - Conclusions - E2- and syntenin-containing exosomes are a major type of particle released from cells expressing high levels of syntenin. Efficient production of E2-coated exosomes renders HCV infectivity less susceptible to antibody neutralization in hepatoma cells and PHHs. - Lay summary - This study identifies a key role for syntenin in the regulation of E2 secretion via exosomes. Efficient production of E2-coated exosomes was shown to make hepatitis C virus less sensitive to antibody neutralization. These results may have implications for the development of a hepatitis C virus vaccine.
Available online 15 March 2019
Gesehen am 17.10.2019